Synthesis and evaluation of new anti-microbial additive based on pyrimidine derivative incorporated physically into polyurethane varnish for surface coating and into printing ink paste - H. Abd El-Wahab; Tamer S. Saleh; Ehab M. Zayed; A.S. El-Sayed; Ramy S.A. Assaker (Egyptian Journal of Petroleum)
In this study, heterocyclic compounds containing 3-((4-bromophenyl)diazenyl)-5-(methylthio)-6-(phenylsulfonyl)pyrazolo-[1,5-a]pyrimidine-2,7-diamine (compound II) and 4-(methylthio)-3-phenylsulfonyl)benzo[4,5]imidazo[1,2-a]pyrimidin-2-amine (compound III) were prepared and their chemical structures were confirmed by spectral data. The new compounds were screened for antimicrobial activity against six different microbial strains when physically incorporated into polyurethane varnish formula and printing ink paste. Experimental coatings were manufactured on laboratory scale and applied by brush onto glass and steel panels. Results of the biological activity indicated that polyurethane varnishes and printing ink paste containing compounds II and III exhibit a very good antimicrobial effect. The physical and mechanical resistances of the polyurethane varnish formulations were also studied to evaluate any drawbacks associated with this addition. The studies revealed that the physical incorporation of compounds II and III enhances slightly the physical and mechanical properties.